Association between psychological stress and stimulation of inflammatory responses in periodontal disease. - Mahvash Mousavijazi; Aniseh Naderan; Mitra Ebrahimpoor; Maryam Sadeghipoor (Tehran University of Medical Sciences, 2013)
Based on the evidence regarding the relationship between inflammatory processes and stress responses, the present study investigated the association between psychological stress and elevation of inflammatory mediators related to periodontal disease in adult patients.The study consisted of 50 patients including 25 patients with chronic periodontitis and 25 cases with aggressive periodontitis. Twenty-five healthy subjects without any evidence of periodontal disorder were also randomly selected as the control group. The clinical parameters including plaque index (PI), bleeding on probing (BOP), probing depth (PPD) and clinical attachment loss (CAL) were recorded and GCF samples were collected for analysis of GCF contents of IL-6 and IL-1β levels. The Kettle stress questionnaire was also used to determine stress severity.IL-1β was significantly higher, but IL-6 was only slightly higher(marginal p-value=0.058)The median score of stress was higher in aggressive periodontitis than the chronic disorder and also in the two periodontal disease groups than the healthy subjects. Among studied clinical parameters, CAL and PPD were positively correlated with the GCF IL-1β level. No significant correlations were found between clinical parameters and GCF IL-6 level. There were strong positive relationships between stress severity and in both aggressive and chronic periodontitis; however stress did not influence GCF contents of IL-6.Psychological stress has a pivotal role in the stimulation of inflammatory processes via IL-1β increase in aggressive and chronic periodontitis.